Transplantation of Normal Adipose Tissue Improves Blood Flow and Reduces Inflammation in High Fat Fed Mice With Hindlimb Ischemia - Chen, Liyuan; Wang, Lin; Li, Yongjie; Wuang, Liqun; Liu, Yaofang; Pang, Ningbo; Luo, Yulin; He, Jing; Zhang, Liping; Chen, Ni; Li, Rong; Wu, Jianbo (Frontiers in Physiology, 2018)
Background: Fat deposition is associated with peripheral arterial disease. Adipose tissue has recently been implicated in vascular remodeling and angiogenic activity. We hypothesized that the transplantation of adipose tissues from normal mice improves blood flow perfusion and neovascularization in high-fat diet fed mice. Methods: After 14 weeks of high-fat diet (HFD)-fed mice, unilateral hind limb ischemia was performed. Subcutaneous white adipose tissue (WAT) and brown adipose tissue (BAT) fat pads were harvested from normal EGFP mice, and subcutaneously transplanted over the region of the adductor muscles of HFD mice. Blood flow was measured using Laser Doppler Scanner. Vascular density, macrophages infiltration, and macrophage polarization were examined by RT-qPCR, and immunohistochemistry. Results: We found that the transplantation of WAT derived from normal mice improved functional blood flow in HFD-fed mice compared to mice transplanted with BAT and sham-treated mice. WAT transplantation increased the recruitment of pericytes associated with nascent blood vessels, but did not affect capillary formation. Furthermore, transplantation of WAT prevented HFD-induced insulin resistance, M2 macrophage predominance and the release of arteriogenic factors in ischemic muscles. Mice receiving WAT also displayed a marked reduction in several proinflammatory cytokines. In contrast, mice transplanted with BAT were glucose intolerant and demonstrated increased IL-6 levels in ischemic muscles. Conclusion: These results indicate that transplantation of adipose tissue elicits improvements in blood perfusion and beneficial effects on systemic glucose homeostasis and could be a promising therapeutic option for the treatment of diabetic peripheral arterial disease.